SUN-916 Novel Germline p.Gly42Arg MEN1 Missense Mutation in a Family Harboring Very Aggressive Pancreatic Tumor, Hyperparathyroidism and Pituitary Tumor - Naves, Luciana Ansaneli (J Endocr Soc, 2020)
Background.Pancreatic neuroendocrine tumors ocurs in 30-80% of patients with MEN-1, and may be non-functioning and hormone secreting tumors. Non-functioning GEP-NETs are increasingly recognised due to advanced imaging modalities such as endoscopic ultrasound thus became the most common type in MEN1 patients. Several mutations MENIN gene were described, although patients with missense mutations are considered as low-impact mutation carriers.Case report.Index case, female, 47 years old, menarche at age of 16yo, amenorrhea until 23yo, when started continuous oral contraceptives. At age of 45 presented dizziness, paresthesia, cramps, had the diagnosis of Hyperparathyroidism related to multinodular parathyroid hyperplasia (Calcium 14mg/dL, PTH 117 pg/mL) and macroprolactinoma (prolactin 235 ng/mL; pituitary tumor 1.2 X 1.0 cm). All siblings and her mother were recruited and one brother, aged 45 years confirmed the diagnosis of hyperparathyroidism and nephrocalcinosis. Their mother, aged 77 years old, presented abdominal pain, and had the diagnosis of aggressivepancreatic tumor compressing bile duct causing intra and extra-pancreatic dilation, associated with metastatic lymph nodes. She was sunmitted to total pancreato-gastrectomy with esophagus jejunum anastomosis. Genetic screening:MEN1genetic screening for mutations was performed in all patients. In these probands, MLPA analysis was performed to detect large deletions of the MEN1gene, using SALSA MLPA probemix kit P017-D1 according to the manufacturer’s instructions (MRC-Holland, Amsterdam, The Netherlands).DNA was extracted from EDTA-Whole blood using MagNA Pure 24 (Roche). Sequencing libraries were qualified/quantified using TapeStation4200 (Agilent). Test method included coding regions ±10bp flanking intronic sequences of 3921 genes enriched using Kappa HyperPlus Library Preparation Kit (Roche) and SeqCap EZ inherited disease panel (Roche) and sequenced (2x75-bp Mid Output V2 Reagent) using NextSeq-500 (Illumina) (estimated mean coverage-100X). Read alignment, variant calling, variant filtration and annotation were performed with Varstation. SNVs and small indels (20bp) with total-read-depth,10X and variant-read-frequency more than20% found on AIP, APC, CDC73, CDKN1B, DICER1, FH, MAX, MEN1, MET, NF1, PRKAR1A, PTEN, RET, SDHA, SDHAF2, SDHB, SDHC, SDHD, TMEM127, TP53, VHL, WRN genes were analyzed.A missense mutation in exon 2, MEN1:c.124G.C:p.(GLY42Arg) was detected. Discussion and conclusion:MEN1-associated GEP-NETs seem to have a low proliferation rate and long survival has been reported, they should be of particular attention, since they are still the principal cause of death in MEN1 patients.Early screening and diagnosis are crucial for MEN-1 phenotypes.